Overview of Newer Glucocorticosteroid Preparations for Inflammatory Bowel Disease - R Brattsand (Canadian Journal of Gastroenterology)
Because the glucocorticosteroid receptor seems to be uniform in the human body, there is currently no support for a possibility of separating the therapeutic and adverse glucocorticosteroid actions at the receptor level. However, based on a new generation of glucocorticosteroids characterized by a high first pass metabolism in the liver, it seems possible today co reach a more selective topical therapy of inflammatory bowel disease. The properties of three new glucocorticosteroids are presented: the highly potent budesonide, fluticasone propionate and tixocortol pivalate - the latter with only low topical potency. Their properties can be exemplified by budesonide, which is currently the best documented compound. The topical potency of budesonide is 200 and 15 times higher than chose of hydrocortisone and prednisolone, respectively. This means that there is a high potential for anti-inflammatory and immunosuppressive actions on rectal and bowel mucosa. The compound is metabolically stable in the bowel compartment, which allows full retention of glucocorticosteroid activity in the target organ. However, when absorbed and distributed to the liver, there is a 90% first pass hepatic metabolism co metabolites of very low potency. This suggests that after topical application to rectal or bowel mucosa, glucocorticosteroid activity in the systemic circulation is low. This is in contrast to prednisolone, which has a hepatic first pass metabolism of just 20%.